Estudo de ferramentas de computação gráfica no processo de desenvolvimento conceitual de produtos - Silva, Lucas Stein da (2020)
Due to the importance of the creation process, and integration in product development, it is necessary to study and implement effective procedures and tools for designing good solutions. The present dissertation shows the study of a procedure for applying Computer Graphics (CG) in Process and Product Development (PDP). The procedure is intended to serve as a basis for selecting computational techniques and tools to assist in product design activities through tridimensional modeling. The pretension of the procedure is that besides helping the designer in the conceptual development activity of a product, that the good application of the computer graphics tools brings benefits to other stages of the product development process, bringing integral information to the other members of the team of project. The development of this project is based on the studies of three-dimensional modeling and design methodologies, from which parameters were generated for the selection of tools aimed at application in design, specifically in the conceptual development of the product, resulting in considerations for their use. Later, a case study will be carried out, in which a product of the agricultural machinery segment will be developed, through the application of the tools and the proposed procedure. The main results are summarized in the process of selecting the computational tools, and in their application, where the 3D modeling software with the freest modeling flow eventually stood out due to the possibilities they offer regarding the fast and intuitive model creation. Thus, it was possible to conclude that there are large differences between the software that are generally considered the same category, which makes their careful classification important, benefiting the subsequent steps of the mechanical design of the product.